Prevalence of Typhoid Fever among Different Socio-Demographic Groups in District Bahawalnagar, Pakistan: Prevalence of Typhoid Fever - Ishtiaq, Abir; Khalil, Sidra; Khalil, Samina; Ahmed, Farhan; Ahmad, Bilal; Ghaffar, Abdul; Khalid, Muhammad; Azam, Sheikh Muhammad; Imran, Muhammad (Pakistan Journal of Health Sciences, 2023)
Typhoid is an infectious disease caused by a bacterium Salmonella typhi and this bacterium spreads so fast in non-hygienic conditions. This disease is abundantly found in areas where hygienic conditions are poor. Objective: The objective of the present study was to evaluate the prevalence of typhoid among different socio-demographic groups and gender from the populace of different tehsils of district Bahawalnagar (Pakistan). Methods: The blood samples of suspected patients were collected from the suspected patients belonging various tehsils of Bahawalnagar (Pakistan) during April to July, 2022. Diagnostic test IgG/IgM was performed using test kit. A questionnaire was also used to collect information from all the suspects with questions related to age, gender, month, socioeconomic status, area, source of water for drinking purpose, and source of food. Results: Results showed 66.39% positive cases for S. typhi from a total of 360 suspected patients with apparent symptoms of typhoid fever belonged to various regions of district Bahawalnagar (Pakistan). Significant difference was found in gender-based data, showing significantly (p<0.05) higher occurrence of typhoid fever in females (51.46%) than males (48.54%). Population consuming homemade food was significantly (p<0.05) most affected with the S. typhi. Conclusions: Higher prevalence of typhoid fever was recorded in the females of district Bahawalnagar (Pakistan). An alarming percentage (54.07%) of positive cases for typhoid fever among the populace was also found, consuming water from the local water-filtration-plants of the studied region.